Perubahan Undang-Undang Dasar Negara Republik Indonesia 1945 Melalui Putusan Mahkamah Konstitusi: Studi Terhadap Putusan Nomor 92/PUU-X/2012 - Allan Fatchan Gani Wardhana (Jurnal Hukum IUS QUIA IUSTUM, 2014)
After the reform, the amendment of 1945 Constitution of Republic Indonesia, in fact, keeps taking place. The material of 1945 Constitution of Republic Indonesia was amended not only through the formal mechanism of People’s Consultative Assembly conventions, but also through informal mechanism or the mechanism outside the formal context, in this case, through the interpretation of the judges of Constitutional Court. This research studied the problems about: first, did the Act of Constitutonal Court Number 92/PUU-X/2012 amend 1945 Constitution of Republic Indonesia? Second, what were the juridical implications of the Acts of Constitution Assembly? The research method used was normative juridical using case study. The result of the research concluded that first, there was an amendment of 1945 Constitution of Republic Indonesia through the Act of Constitutional Court of Republic Indonesia Case Number 92/PUU-X/2012 regarding the process of the formulation and discussion of draft law on Regional Representative Council (DPD) authority. Second, the Act of Constitutional Court had an implication on the position of DPD which is now equal to House of Representatives and President in suggesting draft law and in formulating Prolegnas, DPD must be involved.